Implementation Of Partnership-Based Islamic Religious Education Supervision In Integrated Islamic Elementary School (SDIT) Insan Mulia Pekalongan - Rahmi Anekasari (Universitas Negeri Semarang, 2021)
This study aims to describe and analyze the implementation of partnership-based Islamic religious education supervision at SDIT Insan Mulia Pekalongan. This research is a qualitative research, taking the background of SDIT Insan Mulia Pekalongan. Data was collected by conducting observations, in-depth interviews, and documentation. Data analysis is carried out by giving meaning to the data that has been collected, and from that meaning conclusions are drawn. Checking the validity of the data is carried out by triangulating with two modes, namely source triangulation and method triangulation. The results showed that: (1) the implementation of supervision of Islamic religious education at SDIT Insan Mulia Pekalongan was carried out by appointed supervisors, namely supervisors from the Pekalongan Ministry of Religion Office, school principals, and senior teachers. The process of implementing supervision is carried out in several stages or steps, namely preparation which includes coordination and preparation of supervision programs, implementation of supervision, and assessment or evaluation and follow-up. The implementation of supervision of Islamic religious education at SDIT Insan Mulia Pekalongan can be said to have gone well, as evidenced by Islamic religious education teachers getting clearer directions/solutions when facing difficulties, knowing the weaknesses and shortcomings so as to provide future input and the implementation of Islamic religious education learning has been going well. (2) the implementation of supervision of Islamic religious education at SDIT Insan Mulia Pekalongan is included in the category of the democratic type. This is evidenced by the implementation of supervision that runs democratically, namely the existence of a collaboration carried out by all parties in the school, the existence of reciprocity between supervisors and religious teachers, not imposing their will, giving each other inputs and ideas without any dropping each other, teachers are given the authority to develop Islamic religious education learning, and supervision activities are carried out in a flexible (not authoritarian) manner.